Downregulation of microRNA‐15a‐3p is correlated with clinical outcome and negatively regulates cancer proliferation and migration in human osteosarcoma. Issue 1 (18th September 2017) - Shi, Jiyuan; Fu, Qiang; Yang, Pei; Liu, Huitong; Ji, Le; Wang, Kunzheng
Abstract: In this study, we investigated the expression, correlation to clinical outcomes and biological functions of microRNA‐15a‐3p (miR‐15a‐3p) in human osteosarcoma. MiR‐15a‐3p expressions in osteosarcoma cell lines and clinical tissues of osteosarcoma patients were measured by qPCR. Relevance of endogenous miR‐15a‐3p to osteosarcoma patients' clinicopathological factors or overall survival was statistically analyzed. In addition, the independence of miR‐15a‐3p predicting cancer patients' overall survival was analyzed by Cox regression method. Furthermore, in osteosarcoma cell lines, Saos‐2 and HOS cells, miR‐15a‐3p was overexpressed through stable lentiviral transduction. The functional regulations of miR‐15a‐3p overexpression on cancer ell proliferation and migration were then analyzed. MiR‐15a‐3p was significantly downregulated in osteosarcoma cell lines and human osteosarcoma tumors. Downregulation of endogenous miR‐15a‐3p in osteosarcoma tumors was significantly associated with cancer patient's poor clinical outcomes and low survival rate. Also, endogenous miR‐15a‐3p was confirmed to be an independent biomarker for predicating cancer patients' survival. In Saos‐2 and HOS cells, lentivirus‐induced miR‐15a‐3p overexpression had significantly tumor suppressing functions, by inhibiting both proliferation and migration. Significant downregulation of miR‐15a‐3p in osteosarcoma may be an independent biomarker to predicting cancer patients' poor prognosis. Overexpression miR‐15a‐3p may be an efficient functional meaning to suppress osteosarcoma development. Abstract : Significant downregulation of miR‐15a‐3p in osteosarcoma may be an independent biomarker to predicting cancer patients' poor prognosis. Overexpression miR‐15a‐3p may be an efficient functional meaning to suppress osteosarcoma development.